2011
DOI: 10.1016/j.nano.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of siRNA into breast cancer cells via phage fusion protein-targeted liposomes

Abstract: Efficacy of siRNAs as potential anticancer therapeutics can be increased by their targeted delivery into cancer cells via tumor-specific ligands. Phage display offers an unique approach to identify highly specific and selective ligands that can deliver nanocarriers to the site of disease. In this study, we proved a novel approach for intracellular delivery of siRNAs into breast cancer cells through their encapsulation into liposomes targeted to the tumor cells with preselected intact phage proteins. The target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 34 publications
0
62
1
Order By: Relevance
“…Recently, Bedi et al, demonstrated phage-targeted siRNA nanopharmaceuticals through their encapsulation into liposomes targeted to the breast tumor cells with preselected intact phage proteins [20]. "The presence of pVIII coat protein fused to a MCF-7 cell-targeting peptide "DMPGTVLP" in the liposomes was confirmed by Western blotting.…”
Section: Phage Displaymentioning
confidence: 99%
“…Recently, Bedi et al, demonstrated phage-targeted siRNA nanopharmaceuticals through their encapsulation into liposomes targeted to the breast tumor cells with preselected intact phage proteins [20]. "The presence of pVIII coat protein fused to a MCF-7 cell-targeting peptide "DMPGTVLP" in the liposomes was confirmed by Western blotting.…”
Section: Phage Displaymentioning
confidence: 99%
“…In a different approach, a phage display-selected ligand targeting breast cancer cells was incorporated in liposomes containing siRNA. The delivered liposomes were shown to significantly downregulate the PRDM14 gene in the MCF7 target cells (Bedi et al, 2011). In addition, the option to directly use bacteriophages as drug-delivery platforms has been explored.…”
Section: Viral Drug Delivery Systemsmentioning
confidence: 99%
“…Multi-Walled Carbon Nanotubes (MWCNTs), Boron Nitride Nanotubes (BNNTs), Amorphous Boron Nitride Nanotubes (a-BNNTs) and Hexagonal Boron Nitride Nanotubes (h-BNNTs) for eliminating carcinoma, sarcoma, lymphoma, leukemia, germ cell tumor and blastoma cancer cells and tissues from human blood are a new form of nanotubes with unique characteristics such as small size, high area specific surface, a hollow tube-like structure, high mechanical strength, and considerable electrical conductivity [164][165][166][167][168][169][170][171][172][173]. Nanotubes are classified as single-walled (SWNTs) and multi-walled (MWNTs).…”
Section: Introductionmentioning
confidence: 99%
“…They can show a behavior similar to that of metals or semi-conductors depending on their diameter and characteristics. These behaviors usually originate from the development and arrangement of their Nanolayers [164][165][166][167][168][169][170][171][172][173].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation